1978
DOI: 10.1073/pnas.75.2.955
|View full text |Cite
|
Sign up to set email alerts
|

Antibody response of mice to chemically induced tumors.

Abstract: BALB/c mice immunized with syngeneic methylcholanthrene-induced fibrosarcomas did not have antibodies against the unique tumor-specific transplantation antigens, even though they were capable of rejecting a lethal dose of tumor cells. Endogenous murine leukemia virus antigens expressed by certain of the tumors did, however, elicit high titers of antibodies, accounting for serological crossreactions that occurred between those tumors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

1978
1978
2000
2000

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(18 citation statements)
references
References 24 publications
1
17
0
Order By: Relevance
“…Similarly, antisera raised against the two ascites tumors only showed weak to moderate cross-reactions with R~ST-L1 cells in vitro. This is in agreement with other investigators who have observed dissociation between rejection antigens and serologically detectable antigens (1,6).…”
Section: Discussionsupporting
confidence: 82%
“…Similarly, antisera raised against the two ascites tumors only showed weak to moderate cross-reactions with R~ST-L1 cells in vitro. This is in agreement with other investigators who have observed dissociation between rejection antigens and serologically detectable antigens (1,6).…”
Section: Discussionsupporting
confidence: 82%
“…Serological identification of these antigens would clearly facilitate their analysis, but this has proved to be more difficult than expected. Mouse sarcomas frequently express antigens related to murine leukemia viruses (MuLV) and mouse sera frequently contain natural antibodies to MuLV-related antigens (6)(7)(8)(9). Unless steps are taken to control for MuLV-related reactions, they can introduce considerable confusion into the serological analysis of mouse sarcomas.…”
mentioning
confidence: 99%
“…(They are auto-anti-idiotypic, as the stimulatory idiotype is endogenous.) Since they appear in mice in the apparent absence of antibodies bearing the anti-tumour idiotype (4,21), it is likely that they are antireceptor antibodies complementary to idiotopes on T cell receptors and T cell factors. A network of similar idiotypes on T cells and their soluble factors, modulated by corresponding anti-idiotypes, has previously been proposed as a regulator of tumour immunity (24).…”
Section: Discussionmentioning
confidence: 99%
“…Humoral immunity is less well characterized, especially as free anti-tumour antibodies are often not detectable (4). Nevertheless, the serum of mice exposed to tumours is not devoid of soluble tumourspecific factors (5)(6)(7).…”
Section: Introductionmentioning
confidence: 99%